2011
DOI: 10.1111/j.1440-1754.2011.02065.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality of Chinese adolescents: Distribution and its associated factors

Abstract: The poor sleep quality of many adolescents may be attributed to various causes, especially psychological reasons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
50
1
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 31 publications
13
50
1
7
Order By: Relevance
“…Extant findings point to the importance of additional studies in this area. Adolescents with sleep problems report experiencing more loneliness than adolescents without sleep problems (Mahon 1994;Xu et al 2012), and young adolescents with a history of chronic loneliness report more sleep problems than their peers (Harris et al 2013). In a 12-month longitudinal study, Roberts et al (2002) found that youth with high levels of sleep problems experienced greater problems in their peer relationships, even after controlling for initial levels of peer functioning.…”
Section: Peer Factorsmentioning
confidence: 99%
“…Extant findings point to the importance of additional studies in this area. Adolescents with sleep problems report experiencing more loneliness than adolescents without sleep problems (Mahon 1994;Xu et al 2012), and young adolescents with a history of chronic loneliness report more sleep problems than their peers (Harris et al 2013). In a 12-month longitudinal study, Roberts et al (2002) found that youth with high levels of sleep problems experienced greater problems in their peer relationships, even after controlling for initial levels of peer functioning.…”
Section: Peer Factorsmentioning
confidence: 99%
“…The relationship between depression and sleep disturbances was so strong that it was one of the diagnostic criteria of major depression [34]. High degree of depression and anxiety were found to be the influencing factors of poor sleep among Chinese adolescents [35].…”
Section: Discussionmentioning
confidence: 99%
“…Çin'de yaşayan gençlerin %54,6'sının uyku sorunu olduğunu saptamışlardır. 23 Suen ve ark. yaptığı çalışmada öğrencilerin %58'inin uyku sorunu yaşadığını saptamışlardır.…”
Section: Yöntemunclassified